Increase the production of giant mud crab (Scylla serata) through the Bieng Samudra Cage in Pauh Tanjung Village River Farmer Group, Langsa City - Fadlon Haser, Teuku; Febri, Suri Purnama; Putri, Kartika Aprilia; Persada, Andri Yusman; Sari, Herlina Putri Endah; Syardiansah, Syardiansah; Syahriandi, Syahriandi; Radhiah, Radhiah; Harahap, Antoni; Acha, Basyarudin (Fakultas Pertanian, Universitas Samudra, 2024)
Potential for the development of the mangrove crab business in the coastal area of the city of Langsa, which has a fairly large mangrove forest area and produces abundant mangrove crab resources. However, some of the results of the study stated that the exploitation and the absence of restrictions on the size of the capture of mangrove crabs resulted in a decrease in the number of catchments by fishermen because the condition of crab stock in nature has decreased. The purpose of dedication is to provide education and training to fishermen about selling mangrove crabs, which is more prioritized than fattening results from direct catches from nature, and to increase the production of mud crabs by utilizing local materials. The next goal is the management of crab capture. Implementation of dedication is carried out through socialization and training for coastal communities and fishermen in Sungai Pauh Tanjung Village, Langsa City. The results of the implementation of community service activities contribute to increasing skills and added value, as well as increasing the production of mangrove crabs through the use of Samudra being cages and the use of local materials as potential feed for fattening mangrove crabs before being sold at the market.